Implications of emissions limitation protocols and concentration stabilisation trajectories for developing (non-annex I) countries - Pryadarshi R. Shukla (Fondazione Eni Enrico Mattei (FEEM), 1998)
The ultimate objective of the Framework Convention on Climate Change is the stabilisation of greenhouse gases concentration in the atmosphere at a level that will prevent dangerous anthropogenic interference with the climate system. A specified stabilisation concentration level can be achieved by infinite emissions trajectories. The analysis in this paper considers two well known emission trajectories (WGI, Working Group I of the IPCC and WRE, Wigley, Richels and Edmonds) and three protocols (Two extremes of the Dutch proposal and a medium case of the French proposal). Since most models are developed in the Annex I nations, they tend to determine the socioeconomic dynamics of Non Annex I nations on lines similar to those of Annex I nations, missing the vital differences among nations, regions and especially between industrialised nations (Annex I) and the developing world (Non-Annex I). A robust climate change agreement should call for participation of all major consituents, and Non-Annex I nations are a very important block. The aim of this paper is to generate information and analysis which highlight the implications of proposed protocols for the Non-Annex I nations and help in arriving at a widely acceptable and implementable climate change agreement.
Keywords: 330; Immissionsschutz; Klimaschutz; Umweltabkommen; Entwicklungsländer